Crises, informalité et reconfigurations du marché du travail : quatre décennies de bouleversements économiques au Brésil - Mireille Razafindrakoto; François Roubaud; Alexis Saludjian (Revue de la Régulation)
This article analyzes the adjustments of the Brazilian labour market over the long term, particularly during periods of macroeconomic crisis, which have spanned more than one third of the last forty years. One of the objectives is to put the various theories of the informal to the test of empirical evidence and in particular the hypothesis of its anticyclical role postulated by the dualist thesis. Empirically, our approach is based on an important work of “statistical archaeology” to reconstruct historical series and first-hand processing of millions of observations of micro-data from surveys or administrative records. Our three approaches converge. Among the main findings, we show the tremendous resilience of the Brazilian labour market, which goes down in history, the gradual disappearance since the 1990s of the mechanisms of the “canonical” crisis, supplanted by a process of multifaceted exclusion, as well as the increasing blurring between formal and informal borders, to the detriment of workers’ rights. However, crises are not always the best starting point: for example, the growth phase of the 2000s appears to be the only “transformative” period which left a positive and lasting imprint on the world of work.